Primaquine for prophylaxis against malaria among nonimmune transmigrants in Irian Jaya, Indonesia. - Baird, J; Fryauff, D; Basri, H; Bangs, M; Subianto, B; Wiady, I; Purnomo; Leksana, B; Masbar, S; Richie, T (1995)
A comparison of primaquine versus chloroquine for prophylaxis among nonimmune transmigrants from Java and Bali in the hyperendemic Arso region of Irian Jaya, Indonesia was conducted. Forty-five subjects received 0.5 mg of primaquine base/kg of body weight every other day, and 54 people in the same village received weekly 5 mg of chloroquine base/kg for 16-19 weeks beginning in December 1992. Plasmodium falciparum accounted for 18 of 30 infections with chloroquine, and four of five infections among subjects receiving primaquine. Plasmodium vivax was found in 12 people taking chloroquine but in just one person taking primaquine. The risk of malaria among people taking chloroquine relative to that among subjects taking primaquine was 3.96 (P = 0.014) for P. falciparum and 10.56 (P = 0.012) for P. vivax. Primaquine was better tolerated than chloroquine. The minimal protective efficacy for primaquine prophylaxis was 74% against P. falciparum and 90% against P. vivax among nonimmune children and adults living in Irian Jaya. These findings require confirmation with randomized, double-blinded, and placebo-controlled trials.